CD274/PD-L1 gene amplification and PD-L1 protein expression are common events in squamous cell carcinoma of the oral cavity - Straub, Melanie; Drecoll, Enken; Pfarr, Nicole; Weichert, Wilko; Langer, Rupert; Hapfelmeier, Alexander; Götz, Carolin; Wolff, Klaus-Dietrich; Kolk, Andreas; Specht, Katja (OncoTarget, 2016)
https://doi.org/10.18632/oncotarget.7593 Melanie Straub, Enken Drecoll, Nicole Pfarr, Wilko Weichert, Rupert Langer, Alexander Hapfelmeier, Carolin Götz, Klaus-Dietrich Wolff, Andreas Kolk, Katja...
Gesehen am 19.02.2020